European Anti-Poverty Policies in the 1990s: Toward a Common Safety Net? - Diane Sainsbury; Ann Morissens (Luxembourg Income Study (LIS), 2002)
Using the notion of the poverty regime as a heuristic device, this paper examines the safety nets of several members of the European Union and three candidate countries: Belgium, France, Germany, the Netherlands, Italy, Spain, the United Kingdom, Denmark, Finland, Sweden, the Czech Republic, Hungary and Poland. It addresses two board issues: 1) Has there been a convergence in the safety nets of these member countries of the European Union during the 1990s? 2) What are the implications of enlargement of the European Union for the creation of a common safety net? Initially several dimensions of the poverty regime are employed to compare the safety nets. Subsequently we analyze the incidence of poverty and poverty reduction for the entire population and vulnerable groups-the unemployed, solo mothers and large families, and the elderly-in the countries using data from the Luxembourg Income Study. In analyzing poverty reduction effectiveness we utilize both relative and absolute measures to gauge the impact of income maintenance policies, distinguishing between the safety net and other transfers. The analysis reveals that during the 1990s the poverty rate increased in most countries and in many instances for vulnerable groups; an exception was the elderly. Means tested benefits assumed growing importance in alleviating poverty, but reforms also produced diversity in the safety nets across Europe. Contrary to earlier theorizing that means tested benefits are marginalized in the social democratic welfare state regime, we find that the safety nets in these countries often equaled or surpassed that of the UK in reducing poverty. Finally, apart from impressive poverty reduction, the policies of the three candidate countries did not form a distinctive poverty regime. Instead they tended to cluster with other member countries.
Keywords: 330; Armutsbekämpfung; Soziale Sicherheit; Öffentliche Sozialleistungen; EU-Staaten